IgG1-4 subclasses in paraproteinemias - Tichý, M; Hrncír, Z (Neoplasma, 1990)
The concentration of IgG1-4 subclasses was determined in a series of 10 IgG1 paraproteinemias (5 multiple myelomas and 5 non-myeloma paraproteinemias) and in a series of 11 IgA paraproteinemias (7 multiple myelomas and 4 non-myeloma paraproteinemias). In the group of IgG1 myelomas, deficiency was established in the subclasses IgG2-4, in the group of IgA myelomas, deficiency was proved in all IgG1-4 subclasses as compared with non-myeloma paraproteinemias. Decreased IgG heterogeneity in IgG1 myelomas was demonstrated by the method of isoelectric focusing.
Keywords: imunoglobulin A; senioři; Paraproteinemias; Middle Aged; Immunoglobulin G; mužské pohlaví; ženské pohlaví; dospělí; Humans; imunoglobulin G; Adult; Female; Aged; Immunoglobulin A; lidé; Male; paraproteinemie; lidé středního věku